Mapping and Identifying a Candidate Gene (Bnmfs) for Female-Male Sterility through Whole-Genome Resequencing and RNA-Seq in Rapeseed (Brassica napus L.) - Teng, Changcai; Du, Dezhi; Xiao, Lu; Yu, Qinglan; Shang, Guoxia; Zhao, Zhigang (Frontiers in Plant Science, 2017)
In oilseed crops, carpel and stamen development play vital roles in pollination and rapeseed yield, but the genetic mechanisms underlying carpel and stamen development remain unclear. Herein, a male- and female-sterile mutant was obtained in offspring of a (Brassica napus cv. Qingyou 14) × (Qingyou 14 × B. rapa landrace Dahuang) cross. Subsequently, F2-F9 populations were generated through selfing of the heterozygote plants among the progeny of each generation. The male- and female-sterility exhibited stable inheritance in successive generations and was controlled by a recessive gene. The mutant kept the same chromosome number (2n=38) as B. napus parent but showed abnormal meiosis for male and female. One candidate gene for the sterility was identified by simple sequence repeat (SSR) and insertion deletion length polymorphism (InDel) markers in F7-F9 plants, and whole-genome resequencing with F8 pools and RNA sequencing with F9 pools. Whole-genome resequencing found three candidate intervals (35.40–35.68, 35.74–35.75 and 45.34–46.45 Mb) on chromosome C3 in Brassica napus and candidate region for Bnmfs was narrowed to approximately 1.11-Mb (45.34–46.45 M) by combining SSR and InDel marker analyses with whole-genome resequencing. From transcriptome profiling in 0-2 mm buds, all of the genes in the candidate interval were detected, and only two genes with significant differences (BnaC03g56670D and BnaC03g56870D) were revealed. BnaC03g56870D was a candidate gene that shared homology with the CYP86C4 gene of Arabidopsis thaliana. Quantitative reverse transcription (qRT)-PCR analysis showed that Bnmfs primarily functioned in flower buds. Thus, sequencing and expression analyses provided evidence that BnaC03g56870D was the candidate gene for male and female sterility in the B. napus mutant.